2013
DOI: 10.3906/sag-1204-111
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine Levels in Allergic Rhinitis and Nasal Polyposis

Abstract: Results of a study designed to examine the behavior of gabion-stepped weirs for energy dissipation are presented in this paper. Laboratory tests were conducted with 8 physical models consisting of 3 diff erent porosities (38%, 40%, and 42%) and 2 slopes (1:1 and 1:2). An iron plate was also placed on each horizontal and vertical step to study and classify the eff ect of step porosity on the energy dissipation rate. A decision tree technique was used to derive if-then rules in order to classify the energy dissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Therefore, ADMA is considered to be associated with endothelial dysfunction. Furthermore, ADMA is considered to be a predictive marker of mortality in critically ill patients (11)(12)(13)(14). Hence, this study was carried out to evaluate asymmetric dimethyl arginine (ADMA) and anti cyclic citrulinated peptide (CCP) in patients with psoriasis.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Therefore, ADMA is considered to be associated with endothelial dysfunction. Furthermore, ADMA is considered to be a predictive marker of mortality in critically ill patients (11)(12)(13)(14). Hence, this study was carried out to evaluate asymmetric dimethyl arginine (ADMA) and anti cyclic citrulinated peptide (CCP) in patients with psoriasis.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Therefore, ADMA is considered to be associated with endothelial dysfunction. Furthermore, ADMA is considered to be a predictive marker of mortality in critically ill patients [ 1 - 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been presumed that ADMA has an important role in the regulation of the L-arginine/ nitric oxide (NO) pathway (15,16). NO has a role in pulmonary physiological regulation of bronchodilation, airway responsiveness, and airway inflammation (16,17). Klein et al reported that elevated ADMA concentration results in the inhibition of NOS that leads to smooth muscle constriction in the airway (17).…”
Section: Introductionmentioning
confidence: 99%
“…ADMA is an endogenous nitric oxide synthase (NOS) inhibitor that contributes to cardiovascular disease pathogenesis related to endothelial dysfunctions such as atherosclerosis, diabetes mellitus, and chronic renal disease (13,14). It has been presumed that ADMA has an important role in the regulation of the L-arginine/ nitric oxide (NO) pathway (15,16). NO has a role in pulmonary physiological regulation of bronchodilation, airway responsiveness, and airway inflammation (16,17).…”
Section: Introductionmentioning
confidence: 99%